Perencanaan Lanskap Sempadan Sungai sebagai Kawasan Rekreasi di Hilir Tukad Yeh Empas, Kabupaten Tabanan - Putra, Aditya Pratama; Asmiwyati, I Gusti Agung Ayu Rai; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap, 2022)
Landscape planning of river border a recreation area in the lower Tukad Yeh Empas, Tabanan Regency. Tukad Yeh Empas is one of the streams in Tabanan Regency that is typically used for irrigation and recreation purposes by the surrounding community, toughTukad Yeh Empas still requires a landscape plan as it shows a detioration tendency of its environment such as water pollution, improper land use change and riverbank erosion.  The purpose of this study is to create a recreation landscape plan of Tukad Yeh Empas.  The method used for this research was surveying using techniques of data collection through the use observation, interviews, questionnaires, and literature study. The stages of this research were preparation, data inventory, data analysis, synthesis, concept development and landscape planning. The data analysis and synthesis carried out information that evaluated the constraints and potencies of the biophysical and socio-cultural conditions and also suggested alternative plans. With the use of spatial analysis and its technique of ranking and scoring the data was applied to alocate recreation zones with the help of Geographycal Information System (GIS). There were three recreational zones: a less potential recreation zone, quite potential recreation zone, and great potential recreational zone. Vegetation that had functions for conservation, cultivation and aesthetics was recommended for this landscape planning. The concept of circulation and facilities was developed according to the user's needs for an attractive recreation without dangering the landscape.